Linking research through design and adult learning programs for urban agendas: a perspective essay - Picchi, Paolo; Oudes, Dirk; Stremke, Sven (Ri-vista. Ricerche per la progettazione del paesaggio, 2020)
Local government are addressing energy transition, one of the prominent sustainability goals in the urban agendas, yet they need to enhance capacity building, therefore engagement with sustainability science and adult learning programs for civil servants are frequently activated. Landscape architects are more frequently called to be boundary spanners in complex sustainability goals. This perspective essay aims at reflecting on the synergetic links between adult learning approaches and landscape architecture research through design in the prominent field of the transition to renewable energy. The reflections will be narrated by means of a first application conducted for the Municipality of Amsterdam. The tentative implications suggests that a social learning environment founds synergetic links to a constructivist research through design approach.